Can trade policy help mobilize financial resources for economic development? - Zdenek Drabek; Sam Laird (World Trade Organization (WTO), 2001)
The linkages between trade and resource mobilization are complex and not well defined in theory. To what extent does trade policy affect resource mobilization and what are the mechanisms? We argue that trade policy is a key factor of influencing the domestic fundamental balance between aggregate savings and investment. The main effect of trade policy on resource mobilization stems from its contribution to static and dynamic gains from trade. But the effect of trade policy on the supply of financial resources also operates through several channels including through linkages of trade policy with foreign investment, government revenues, income distribution, foreign aid. The paper looks at direct and indirect channels, and makes a distinction between short and long term effects of different trade strategies. We also briefly review trade barriers in goods and services affecting developing countries and the potential gains from further liberalization. The long term gains from trade liberalization are substantial, but they may have to be set against short-term adjustments costs. The latter could and should be reduced by effective institutional and tax reforms.
Keywords: F10; F13; O10; O16; 330; Trade policy; finance; foreign investment; income distribution; aid